"Lorenzaccio" di Carmelo Bene: Dalle fonti alla messinscena - Petruzzi, Carlo Alberto (Mimesis Journal, 2020)
The aim of this paper is to provide an analysis of Carmelo Bene’s Lorenzaccio. The archive of the Foundation L’Immemoriale di Carmelo Bene as well as consultations of Bene’s library, enabled to identify literary and philosophical sources of the play. Through the use of several handwritten documents regarding the play, I discuss solutions adopted by Bene to set Lorenzaccio on stage. A brief note in the end of the article confronts the only available version of the work, a television version edited by Mauro Contini.